Analisis Butir Soal Pelajaran Bahasa Arab di MA Roudlotul Ulum Pagak Malang - Siti Fathimah Al Fathiyah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
The focus of this research is to analyze the results of the final exam of the Arabic subjects of the class XI-IPS students in MA Roudlotul Ulum Pagak Malang at odd semester Year lesson 2018/2019. The goal is to allow teachers of Arabic language to make good measuring instruments in measuring students ' level of understanding. The type of research used is quantitative with the data collection model obtained from both, students ' answer and question sheets. The Data obtained is analyzed using anathes and described in a descriptive basis based on the level of validity, reliability, difficulty, power difference and tricky in each multiple choice. The results of the study showed: (1) based on the results of the validity test, it was found that from item question number 1-15, which belongs to the category of valid question only 3 (2.85%) And that belongs to the category of invalid 12 questions (97.15%). (2) Reliability test result indicated that the level of the reliability of mulltiple choice questions 0.54, indicating medium category. (3) The result of difficulty analysis has been known between Question number 1 to 15, there are 8 questions that belong to the category of "Easy", 3 items that belong to the category of "Medium", and 4 items that belong to the category of "difficult" question. (4) Distinguishing power test results show there are 3 questions that include the category of good problem, 3 items including category of medium problem, and the rest is include category of question that can not distinguish between students from Upper group and lower group. Even, the difference in power level is 0 (zero) so there is no discrimination. consequently, the question is revised or unused. (5) The quality of the tricky question has been found there are many problems of tricky questions that need to be revised.